Design, characterisation and drug release study of polymeric, drug‐eluting single layer thin films on the surface of intraocular lenses. Issue 6 (16th July 2020) - Karamitsos, Athanasios; Lamprogiannis, Lampros; Karagkiozaki, Varvara; Laskarakis, Argyrios; Papadopoulou, Lambrini; Fatouros, Dimitrios; Ziakas, Nikolaos; Logothetidis, Stergios; Tsinopoulos, Ioannis
Abstract : To design, develop and study a novel drug delivery system for intraocular applications. The spin coating technique was applied to develop a polymeric, drug‐eluting thin film consisting of a blend of organic polymers [poly (D, L lactide coglycolide) lactide: glycolide 75: 25, PLGA and polycaprolactone, PCL] and dexamethasone on the surface of intraocular lenses (IOLs). The initial durability of the IOLs during spinning was assessed. Information about the structural and optical properties of the modified IOLs was extracted using atomic force microscopy, scanning electron microscopy and spectroscopic ellipsometry. A drug release study was conducted for 8 weeks. The IOLs were durable in spinning speeds higher than the ones used to develop thin films. Single‐layer thin films were successfully developed on the optics and the haptics of the lenses. The films formed nanopores with encapsulated aggregates of dexamethasone. The spectroscopic ellipsometry showed an acceptable optical transparency of the lenses regardless of the deposition of the drug‐eluting films on their surface. The drug release study demonstrated gradual dexamethasone release over the selected period. In conclusion, the novel drug‐eluting IOL system exhibited desired properties regarding its transparency and drug release rate. Further research is necessary to assess their suitability as an intraocular drug delivery system.